Combined Intravenous and Intraarticular Tranexamic Acid Does Not Offer Additional Benefit Compared with Intraarticular Use Alone in Bilateral TKA: A Randomized Controlled Trial. Issue 1 (January 2020) - Meshram, Prashant; Palanisamy, Jeya Venkatesh; Seo, Jong Yeon; Lee, Jong Geun; Kim, Tae Kyun
Abstract: Background: Tranexamic acid (TXA) is efficacious for reducing blood loss and transfusion use in patients who undergo bilateral TKA, and it is administered intravenously alone, intraarticularly alone, or as a combination of these. However, it is unclear whether combined intravenous (IV) and intraarticular TXA offers any additional benefit over intraarticular use alone in patients undergoing bilateral TKA. Questions/purposes: The purposes of our study was to determine (1) whether combined IV and intraarticular TXA reduces blood loss and blood transfusion use compared with intraarticular use alone and (2) whether the frequency of adverse events is different between these routes of administration in patients who undergo simultaneous or staged bilateral TKA. Methods: Between April 2015 and May 2017, one surgeon performed 316 same-day bilateral TKAs and 314 staged bilateral TKAs. Of those, 98% of patients in each same-day TKA (310) and staged bilateral TKA (309) groups were eligible for this randomized trial and all of those patients agreed to participate and were randomized. The study included four groups: simultaneous TKA with intraarticular TXA only (n = 157), simultaneous TKA with IV and intraarticular TXA (n = 153), staged TKA with intraarticular TXA only (n = 156), and staged TKA with IV and intraarticular TXA (n = 155). There were no differences in demographic data among the intraarticular alone and IV plus intraarticular TXA groups of patients who underwent simultaneous or staged bilateral TKA in terms of age, proportion of female patients, BMI, or preoperative hematologic values. The primary outcome variables were total blood loss calculated based on patient blood volume and a drop in the hemoglobin level and administration of blood transfusion. The secondary outcomes of this study were a decrease in the postoperative hemoglobin level; the proportion of patients with a hemoglobin level lower than 7.0, 8.0, or 9.0 g/dL; and the frequencies of symptomatic deep vein thrombosis, symptomatic pulmonary embolism, wound complications, and periprosthetic joint infection. Results: Total blood loss with intraarticular TXA alone in patients undergoing simultaneous bilateral TKA and those undergoing staged procedures was not different from the total blood loss with the combined IV plus intraarticular TXA regimen (1063 mL ± 303 mL versus 1004 mL ± 287 mL, mean difference 59 mL [95% CI -7 to 125]; p = 0.08 and 909 ml ± 283 ml versus 845 ml ± 278 ml; mean difference 64 mL [95% CI 1 to 127]; p = 0.046, respectively). The use of blood transfusions between intraarticular alone and combined IV and intraarticular TXA was also not different among patients undergoing simultaneous (0% [0 of 152] versus 1%; p = 0.149) and staged TKA (1% [1 of 155] versus 0% [0 of 153]; p = 0.98). Furthermore, the frequency of symptomatic thromboembolic events, wound complications, and periprosthetic joint infections was low, without any differences among the groups with the numbers available. Conclusion: Because there was no difference between intraarticular alone and combined intraarticular plus IV regimen of TXA administration, we recommend that IV and intraarticular TXA should not be used in combination. Moreover, other studies have found no differences between intraarticular and IV TXA used alone, and hence to avoid potential complications associated with systemic administration, we recommend that intraarticular alone is sufficient for routine TKA. Level of Evidence: Level I, therapeutic study.